Hydrothermal Vapor‐Phase Fluids on the Seafloor: Evidence From In Situ Observations. Issue 10 (13th May 2020) - Li, Lianfu; Zhang, Xin; Luan, Zhendong; Du, Zengfeng; Xi, Shichuan; Wang, Bing; Lian, Chao; Cao, Lei; Yan, Jun
Abstract: Subseafloor phase separation is a common and significant process in hydrothermal systems and may result in a large of fluid composition differences. The temperatures of hydrothermal fluids are generally considered to be below the associated fluid boiling temperature due to mixing with ambient seawater and the phase separation process. However, we report here shimmering water with temperatures up to 383.3 °C observed in a hot overturned lake at the Yokosuka site, Okinawa Trough, East China Sea, where in situ Raman spectra suggest the presence of a superheated vapor phase. Hydrothermal vents similar to the low‐density hydrothermal system found at the Yokosuka site have also been observed in many other regions. Therefore, much more attention should be given to the impacts of low‐density hydrothermal fluid emanations on marine environments and resource distributions. Plain Language Summary: Hydrothermal systems characterized by the emanations of supercritical‐ and vapor‐phase fluids associated with igneous activities have been observed on mid‐ocean ridges. Here, we report a newly found hydrothermal system dominated by low‐density vapor‐phase fluids at the Yokosuka site, a hydrothermal field located in a backarc basin spreading center. Multiple methods, including in situ Raman spectroscopy measurements, thermocouple sensor measurements, and gas‐tight sampling, were used to investigate this vapor‐phase hydrothermal emanation. In situ observations suggest that the highest temperature (383.3 °C) of the hydrothermal fluids at the Yokosuka site is above the two‐phase boundary of seawater at a depth of 2, 180 m (378.1 °C) and in situ Raman spectra indicate the fluid of the hot overturned lake features a layered structure. Hydrothermal systems with low‐density emanations are likely to be widespread throughout various tectonic settings since similar phenomena have been observed in other hydrothermal fields with conditions close to the phase separation boundary. Key Points: The low‐density vapor‐phase hydrothermal system is observed in the backarc spreading center for the first time In situ Raman spectroscopy measurement was implemented in the vapor‐phase hydrothermal system Implications of low‐density hydrothermal emanations on the deep ocean and mineralization are underestimated than previously thought